Neural Differentiation Is Inhibited through HIF1α/β-Catenin Signaling in Embryoid Bodies - Josef Večeřa; Jana Kudová; Jan Kučera; Lukáš Kubala; Jiří Pacherník (Stem Cells International)
Extensive research in the field of stem cells and developmental biology has revealed evidence of the role of hypoxia as an important factor regulating self-renewal and differentiation. However, comprehensive information about the exact hypoxia-mediated regulatory mechanism of stem cell fate during early embryonic development is still missing. Using a model of embryoid bodies (EBs) derived from murine embryonic stem cells (ESC), we here tried to encrypt the role of hypoxia-inducible factor 1α (HIF1α) in neural fate during spontaneous differentiation. EBs derived from ESC with the ablated gene for HIF1α had abnormally increased neuronal characteristics during differentiation. An increased neural phenotype in Hif1α−/− EBs was accompanied by the disruption of β-catenin signaling together with the increased cytoplasmic degradation of β-catenin. The knock-in of Hif1α, as well as β-catenin ectopic overexpression in Hif1α−/− EBs, induced a reduction in neural markers to the levels observed in wild-type EBs. Interestingly, direct interaction between HIF1α and β-catenin was demonstrated by immunoprecipitation analysis of the nuclear fraction of wild-type EBs. Together, these results emphasize the regulatory role of HIF1α in β-catenin stabilization during spontaneous differentiation, which seems to be a crucial mechanism for the natural inhibition of premature neural differentiation.